2021
DOI: 10.1159/000514930
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Frequency of Daily Toothbrushing and Development of Nonalcoholic Fatty Liver Disease

Abstract: Background & Aims: This study aimed to evaluate the association between the frequency of daily tooth brushing and the development of nonalcoholic fatty liver disease (NAFLD). Methods: A retrospective longitudinal study was conducted from 2005 to 2012 at the Center for Preventive Medicine at St. Luke's International Hospital, Japan. Data on all participants who underwent a health checkup during the study period were collected. NAFLD was diagnosed by abdominal ultrasonography, and all participants who were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Possible reasons for the inconsistency between the results of these studies and the current study are differences in study design, population, measurement and classification of diseases. A few studies have found that a lower frequency of tooth brushing is related to a higher prevalence of liver diseases such as non-alcoholic fatty liver disease [ 25 ] or cirrhosis [ 46 ]. For example, a retrospective and single hospital-based study from Japan (mean age 44) showed that the risk of non-alcoholic fatty liver disease decreased significantly with increasing frequency of brushing teeth, with an OR of 1–2 times daily of 0.85 (95% CI: 0.77–0.95) and 3 times daily of 0.74 (95% CI: 0.67–0.82) compared with those who brush their teeth less than once a day [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible reasons for the inconsistency between the results of these studies and the current study are differences in study design, population, measurement and classification of diseases. A few studies have found that a lower frequency of tooth brushing is related to a higher prevalence of liver diseases such as non-alcoholic fatty liver disease [ 25 ] or cirrhosis [ 46 ]. For example, a retrospective and single hospital-based study from Japan (mean age 44) showed that the risk of non-alcoholic fatty liver disease decreased significantly with increasing frequency of brushing teeth, with an OR of 1–2 times daily of 0.85 (95% CI: 0.77–0.95) and 3 times daily of 0.74 (95% CI: 0.67–0.82) compared with those who brush their teeth less than once a day [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have found that a lower frequency of tooth brushing is related to a higher prevalence of liver diseases such as non-alcoholic fatty liver disease [ 25 ] or cirrhosis [ 46 ]. For example, a retrospective and single hospital-based study from Japan (mean age 44) showed that the risk of non-alcoholic fatty liver disease decreased significantly with increasing frequency of brushing teeth, with an OR of 1–2 times daily of 0.85 (95% CI: 0.77–0.95) and 3 times daily of 0.74 (95% CI: 0.67–0.82) compared with those who brush their teeth less than once a day [ 25 ]. However, this is a single hospital-based study, evaluation by multicenter studies and meta-analyses by different ethnic groups should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies found that lower frequency of teeth brushing is related to higher prevalence of liver diseases, non-alcoholic fatty liver disease 17 or cirrhosis 28 . However, we did not observe associations between toothbrushing and risk of diseases of upper or lower respiratory, and liver or gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Two cohort studies showed an association between poor oral hygiene and higher risk of diabetes 14,15 , whereas another study found no association between them 13 . In addition, oral health behavior has been associated with upper aerodigestive tract cancer risk 16 , liver diseases 13,17 . Nevertheless, the existing studies on the association between oral hygiene behavior and the risk of multiple chronic diseases have not measured the frequency of brushing accurately, and the studies on multi-system diseases and speci c regions in China are very limited.…”
Section: Introductionmentioning
confidence: 99%